An Important Structure in Psychiatric Nursing: Family Resilience - Zekiye Çetinkaya Duman; Ayşe Sarı (Dokuz Eylul University, 2021)
The concept of family resilience is defined as the ability of a family to resist and recover from the hardships experienced by the family. Unlike individual resilience, family resilience focuses on the resilience of the whole family rather than the individual resilience characteristics of the family members through a systemic view of resilience. Three key resilience processes have been identified. These three key processes are the Family Belief Systems, Organization Patterns and Communication /Problem Solving Processes. It is thought that planning of family interventions that will strengthen these resilience processes by nurses working with families is thought to help families cope with crisis situations.